A comprehensive study on the combustion kinetic modeling of typical electronic plastic waste—television set (TV) plastic shell. (3rd June 2021) - Luo, Qiyu; Yao, Zhitong; Qi, Wei; Sun, Jianyuan; Gedanken, Aharon; Chen, Xinyang; Sun, Yuhang; Liu, Jie; Xu, Shaodan; Wu, Weihong
ABSTRACT: Electronic waste is the fastest growing waste stream and one of the most significant constituents is electronic plastics. In this study, the combustion kinetic of typical electronic plastic waste—television set (TV) plastic shell—was investigated using two basic kinetic methods. The reaction mechanism and kinetic compensation effect were probed as well. The thermogravimetric analysis (TGA) revealed that its degradation process can be divided into four stages, namely, reaction initiation stage (20–300 °C), major reaction stage (300–450 °C), minor reaction stage (450–600 °C), and reaction cessation stage (600–1, 000 °C). The activation energy ( E ) were calculated and indicated that, the kinetic parameters from six model-free methods gradually decreased with α increasing from 0.1 to 0.35, and then slightly increased. The Flynn–Wall–Ozawa (FWO) method was more reliable and E values decreased from 155.0 to 147.51 kJ/mol with α range of 0.1–0.35, then gradually increased to 165.21 kJ/mol. Within the Coats–Redfern method, the first-order ( F1 ) model had higher coefficient of determination (R 2 ) and comparable E values with that from FWO method. The result of kinetic compensation effect confirmed that the compensation effect existed between E and A during the plastic waste combustion. A linear relationship ln A = 0.183 E -3.11 (R 2 = 0.991) was obtained. The pre-exponential factors ( A ) were also determined as 7.67 × 10 10 min −1 based on the F1 reaction model and FWO method. Implications : Municipal solid waste (MSW) is a complex mixture of different components and the plastic takes up a significant portion in total MSW. Understanding the combustion process of typical electronic plastic waste and further probing its combustion kinetic are significant. Through this study, it will be significant for the reactor designing and optimizing in practice.